2018
DOI: 10.1007/s10461-018-2069-6
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Predicts Food Insecurity Severity among Persons Living with HIV

Abstract: Food insecurity is a key social and health issue among persons living with HIV (PLHIV). Food insecurity oftentimes co-occurs with substance use, but little is known about the relationship between tobacco use and food insecurity particularly among PLHIV. In this study, we prospectively examined the association of cigarette smoking with food insecurity in a cohort of 108 individuals seeking vocational rehabilitation services. Over the 12-month study period, smokers at baseline reported consistently higher levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 42 publications
0
20
0
2
Order By: Relevance
“…Data from the 2011 to 2012 CHIS demonstrated similar results in a population of young adults, with smoking being more common in food‐insecure young adults (26.9%) than in those with food security (16.4%) . Even though studies continue to demonstrate the association of higher rates of smoking in those with food insecurity, the underlying relationship is likely complex and bidirectional …”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Data from the 2011 to 2012 CHIS demonstrated similar results in a population of young adults, with smoking being more common in food‐insecure young adults (26.9%) than in those with food security (16.4%) . Even though studies continue to demonstrate the association of higher rates of smoking in those with food insecurity, the underlying relationship is likely complex and bidirectional …”
Section: Introductionmentioning
confidence: 84%
“…21 Even though studies continue to demonstrate the association of higher rates of smoking in those with food insecurity, the underlying relationship is likely complex and bidirectional. 23 Research into the relationships between food insecurity and chronic disease has also demonstrated increased utilization of health care in individuals with food insecurity. Data from the 2011 NHIS showed that individuals with food insecurity had higher annual health care expenditures than those who were food secure ($6072 vs $4208, P < .0001) and that this relationship of increased annual costs held across subgroups of food-insecure and food-secure patients with diabetes, hypertension, or heart disease.…”
Section: Food Insecurity and Chronic Diseasementioning
confidence: 99%
“…32 33 Food insecurity among PLHIV is associated with decreased mental and physical health status, 34 suboptimal adherence to ART, 35 use of illicit substances, 36 and increased HIVrelated morbidity and HIV mortality. 37 Important limitations of the studies investigating smoking among PLHIV include that they were conducted among predominantly male populations living with HIV, [38][39][40] lacked granularity in the smoking variable 38 40 or did not examine smoking severity. 39 40 Given that tobacco use is the most important preventable cause of excess mortality worldwide, 1 2 with increased health consequences to PLHIV and WLWH specifically, expanding our understanding of the role of food insecurity as a potentially modifiable factor among WLWH is vital to reducing these health disparities.…”
Section: Open Accessmentioning
confidence: 99%
“… 37 Important limitations of the studies investigating smoking among PLHIV include that they were conducted among predominantly male populations living with HIV, 38–40 lacked granularity in the smoking variable 38 40 or did not examine smoking severity. 39 40 Given that tobacco use is the most important preventable cause of excess mortality worldwide, 1 2 with increased health consequences to PLHIV and WLWH specifically, expanding our understanding of the role of food insecurity as a potentially modifiable factor among WLWH is vital to reducing these health disparities. Therefore, we conducted an analysis of data from the Women’s Interagency HIV Study (WIHS) to understand the associations between food insecurity and smoking over time.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these cross-sectional studies showed that cigarette smoking is a risk factor for food insecurity,23–26 but conversely, some reported that food insecurity may be a risk factor for current smoking27–29 while others reported no evidence of association between smoking and food insecurity 30 31. Three studies conducted in the USA used longitudinal data 32–34. One found that cigarette smoking status at baseline predicted greater food insecurity severity at 12-month follow-up;32 however, another study found that among baseline non-smokers, becoming food insecure was independently associated with a higher likelihood of starting smoking at follow-up,33 and the third study found evidence of a longitudinal bidirectional association between smoking and food insecurity 34.…”
Section: Introductionmentioning
confidence: 99%